Values Versus Constraints: Unpacking the Sustainable Consumption Paradox in Modest Fashion Among Gen Z in Bangladesh - Daizy, Afroza Haque (European Scientific Journal, ESJ, 2026)
Background: With the increasing environmental and ethical challenges that the fashion industry faces, sustainable consumption has become a defining point of concern. This paper is a research into the mismatch between the increased awareness and real-world sustainable buying activities among Generation Z and how modest fashion, sustainability, and consumer attitudes of young customers are influenced. Methods: Mixed-method research was conducted on modest fashion among Generation Z students in Bangladesh. The researchers used a combination of quantitative surveys and qualitative open-ended responses, using a framework on which awareness, attitudes, and practices were measured at a single time point. Convenience Sampling was used to select the participants as university students of Bangladesh, where Gen Z, aged 18 -29, who purchase or even consider modest apparel, so as to include a wide range of gender, socioeconomic, and academic backgrounds, 48 students answered the questionnaire. The questionnaire contained Likert questions about demographics, purchasing frequency, knowledge, motivations, barriers, and social -media influence, as well as open-ended questions on the expectations of the brand and sustainability incentives. Descriptive statistics and correlation were created by SPSS and thematic analysis was used to identify trends in values, constraints and aspirations in the background of consumption behaviour. Results: Results indicate that 77.1% of the participants were familiar with the concept of sustainable fashion, but there was a strong attitudinal-behaviour gap. In particular, 64.6% of the participants mentioned personal style as the main motivation of modest fashion, with only a small proportion of those who always performed sustainable purchases. The correlation analysis demonstrates that there is a moderate positive correlation between the awareness of sustainable fashion and the actual sustainable behaviour among the Gen Z modest fashion consumers (r = 0.384, p = 0.007). It implies that sustainability-aware individuals will more likely make sustainable decisions, including making purchases of environmentally friendly products, purchasing second-hand, or mending clothes. The information thus highlights a serious gap between knowledge and action that must be closed through concerted action among the stakeholders, increased consumer education, facilitation, and innovation of the industry to close the gap. Conclusion: The study provides practical information and can be used to promote a change towards ethical behavior in the modest fashion industry and the wider market by explaining the major drivers, obstacles, and anticipations of Gen Z buyers in their purchasing patterns. These findings imply the incorporation of digital platforms, open supply stores, and peer-driven campaigns to enhance the influence of Gen Z on sustainable consumption in all world markets.